THE EVENT: between Foucault and Deleuze - Lopes, Luiz Manoel (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2024)
Philosophy in the 21st century, by bringing the influences of Deleuze's productions around the event and meaning which we find in his book Logic of Sense published in 1969, gains varied aspects around the positions of the problems to come. The motivations of this work are to monitor the extent to which Michel Foucault and Gilles Deleuze, each in their own way, seek to do philosophy outside the canons, especially when they seek to think outside the philosophy of history and structuralism.